2017
DOI: 10.1016/j.tjog.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome after conservative management of abnormally invasive placenta

Abstract: In this small series, we observed a low successful uterine preservation rate and a high maternal complication rate. We recommend that primary cesarean hysterectomy should be used as the treatment of choice for mild to severe abnormally invasive placenta. Conservative management should be reserved for women with a strong fertility desire and women with extensive disease that precludes primary hysterectomy due to surgical difficulty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…A report that included three patients with conservatively managed placenta percreta after 24 weeks of pregnancy found no success with this approach; furthermore, severe maternal complications were observed. 8 The similarly low success rate for placenta percreta observed in the present systematic review could reflect the severity of placental invasion.…”
Section: Discussionmentioning
confidence: 65%
“…A report that included three patients with conservatively managed placenta percreta after 24 weeks of pregnancy found no success with this approach; furthermore, severe maternal complications were observed. 8 The similarly low success rate for placenta percreta observed in the present systematic review could reflect the severity of placental invasion.…”
Section: Discussionmentioning
confidence: 65%
“…Su et al . reported that placenta in situ management yielded a low success rate and increased maternal morbidity, including hysterectomy because of bleeding . Accordingly, partial removal and in situ management are at risk for requiring uterine artery embolization or hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in current clinical practice, a counterplan should be considered during placental delivery in both vaginal and cesarean delivery. Conservative management without placental delivery is an option for placenta accreta . This approach may avoid hysterectomy without causing damage to the uterine myometrium; however, there is still a risk for secondary postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…accreta (superficial invasion), increta (invasion deeper into myometrium) and percreta (invasion into or through the uterine wall); due to a defect in the decidua basalis (6). Predisposing factors include advanced maternal age, multiparity, history of uterine surgery such as caesarean section, uterine curettage or myomectomy (2,3,7). With the advancement in radiological imaging, the diagnosis of AIP can usually be established prenatally between 18-37 weeks (7).…”
Section: Discussionmentioning
confidence: 99%